Fabricating Pt-decorated three dimensional N-doped carbon porous microspherical cavity catalyst for advanced oxygen reduction reaction. (March 2018) - Cheng, Yaru; Lu, Huiting; Zhang, Kai; Yang, Fan; Dai, Wenhao; Liu, Conghui; Dong, Haifeng; Zhang, Xueji
Abstract: Abundant and low-cost materials with high electrochemical catalytic activity for oxygen reduction reaction (ORR) are in urgent demand for energy storage and conversion devices. In this work, an advanced ORR electrocatalyst of Pt-decorated three dimensional (3D) N -doped carbon porous microspherical cavity (PtN/C PMC) was fabricated by using polystyrene microspheres (PS) as template, and dopamine and K2 PtCl6 as precursors. Microscopic and spectroscopic characterizations revealed large surface area available and affluent pore structures were observed in the resulted PtN/C PMCs, and numerous Pt nanoparticles (NPs) with active (111) facet were decorated on the surface of N/C PMCs. The proposed PtN/C CMCs presented good onset potential, remarkable mass activity (MA) and specific activity (SA), superb methanol tolerance and excellent durability toward ORR in alkaline solutions. The numerous decorated Pt with high active (111) facet coupled with high content of active pyridinic and graphitic nitrogen synergistically contributed to the enhanced ORR activity, while the unique 3D porous structures facilitated O2 and electrolyte transport during the ORR process. This work may open new avenue for designing advanced and cost-effective Pt-based ORR catalyst. Graphical abstract: Image 1